KELEMBAGAAN TATANIAGA KEDELAI DI KABUPATEN GROBOGAN - Efriyani Sumastuti (ECONBANK: Journal of Economics and Banking, 2019)
ABSTRACT The purpose of this study is to map soybean value chain which is directed at institutional development that is synergistic by paying attention to ABGC partnerships (Academic, Business, Government and Community). Determination of the sample is done by purposive sampling quota for respondents targeting input suppliers, soybean farmers, traders (middlemen and traders from village to provincial level), and retailers. For respondents stakeholders (academics, government, business people, and Gapoktan) were selected by proportional purposive sampling. The results showed that the local soybean trading system (from the aspect of distribution and consumption) in the research area through five stages from the first producer farmers to small and medium traders. Then from the two traders it was sold to wholesalers and processing industries. The products processed are distributed to consumers directly or through traders / retailers. Imported soybean trading flow through importers to distributors, then distributed to wholesalers and then distributed to retailers, processing industries and end consumers. The institution of soybean trading seen from the distribution aspect has three functions, namely the exchange function, physical function and function of the facility. The soybean trading system institutional model is formulated in 3 scenarios, namely the soybean trading system institutional model while still being handled by Bulog (Scenario 1); the existing soybean trading system institutional model (scenario 2) and the soybean trading system institutional model proposed by the researcher (scenario 3). In the institutional model of trading system scenario 3, it is broken down based on the work area and divided into 5 regions, namely the central, provincial, district / city, sub-district and village levels